Impactos causados pela privatização no ambiente de trabalho, relações interpessoais e perfil profissional : o caso Embratel - Vilhena, Rosa Maria de Paula (2001)
The goal of work present was to verify the impact of the privatization in the working environrnent, interpersonal relations and professional pro file of the employees of Embratel. So much, it studies the trajectory of the company in the state owned company context, the consolidation transition and process as c10set company of a higly competitive segment. The first chapter introduces the history of the communications in Brazil, the politican-economic implications, the appearance and EmbrateI. The chapter second studies the corporative culture and your importance in feasible of the human resources. The third chapter analyses the pertaining to a group formations and the relationship in the working environrnent. The chapter four investigates the new human resources policies and the element that constitute the professional profile demanded by market. Chapter five studies c1imate organizacional and interfaces with the motivation and the sarisfaction in work. The chapter six analyses the human resources management in Embratel along his existence as state owned company and the privatization. The seventh chapter introduces and analyses the c1imate organizacional research accomplished by the company in 2000. Among the main studies aspects it verifies: Embratel initiated his modemization process before the privatization and that came to accelerate and to introduce new direction for the company. Your administration was until then prejudiced by the mIes and assistance ecsses to political interest, what it checked your little agility. The employee's relation with the company modified. The new vision and the human resources modem policies today offer support to effect the wished and necessary changes, but also they demand adaptability higt degree of alI.